Sobre o teorema de fibração de Milnor - Guerrero Vejarano, Darwin Emerson [UNESP] (2014)
The Milnor bration appears as the main tool in the topological local study of real and complex analytic singularities. In this work we study the famous Milnor Fibration Theorem, and the surprising topological behavior of the Milnor bres. To reach these objectives we use some tools of classical Algebraic Geometry, Complex Analysis of several variables and also some aspects of Morse Theory